Real consequences matters: why hypothetical biases in the valuation of time persist even in controlled lab experiments - Ondřej Krčál; Rostislav Staněk; Bára Karlínová; Stefanie Peer (Masaryk University, Faculty of Economics and Administration, 2019)
In a controlled lab experiment, we investigate hypothetical biases in the value of time by comparing stated preference (SP) and revealed preference (RP) values attached to unexpected waiting times. The SP and RP choice sets are identical in terms of design with the only difference being that the RP choices have real consequences in terms of unexpected waiting times and monetary incentives. We find a substantial hypothetical bias with the average SP value of time being only 71% of the corresponding RP value. The bias is mainly driven by participants who have scheduling constraints during the time of the unexpected wait. Scheduling constraints are taken into account to a much lesser extent in the SP setting than in the RP setting, presumably because only in the latter, the consequences of ignoring them are costly. We find evidence that this effect is stronger for persons with relatively low cognitive ability.
Keywords: 330; valuation of time; hypothetical bias; stated preference; revealed preference; waiting time